Rozdíly v charakteristických vlastnostech a funkcích invariantních NKT buněk zdravých dárců - Dostálová, Karolína (Jihočeská univerzita, 2020)
iNKT cells are a subset of T cells, they express the same phenotypic markers usually found on T and natural killer (NK) cells. They comprise a lineage of CD1d-restricted glycolipid-reactive T lymphocytes which have an important role in imunity. They play critical role in the regulation of many different types of immune responses, ranging from self-tolerance and development of autoimmunity to responses to pathogens and tumors. These cells are gaining increasing importance in health care, particularly in hematooncology. In this study we examined the essential features and functions of Invariant Natural killer T cell (iNKT cells).iNKT cells were isolated from mononuclear cells (MNCs) of healthy donors. Then they were cultured under appropriate conditions in vitro. After reaching sufficient concentration and purity the iNKT cells were used for cytotoxic and immunomodulatory assays and immunophenotype determination. Our results showed that iNKT cells have varying qualities across donors and that they have a heterogeneous immunophenotype, cytotoxic and immunomodulatory potential.
Differencies in charasteristics and functions of invaritant NK T-cells of healthy donors
Keywords: lymfocyt; invariantní NKT buňka; iNKT buňka; cytotoxický efekt; imunomodulace